2010
DOI: 10.1016/j.bbmt.2010.05.009
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Human Herpes Virus 6-Associated Encephalitis/Myelitis following a Second Unrelated Cord Blood Transplantation

Abstract: Human herpes virus (HHV)6-associated limbic encephalitis and/or myelitis is one of the life-threatening central nervous system complications following allogeneic hematopoietic stem cell transplantation (HSCT). Recent reports have shown significant correlations of these complications with unrelated cord blood transplantation (UCBT). We retrospectively analyzed 228 allogeneic HSCT recipients in our single institution; 13 patients (5.7%) were diagnosed with HHV6-associated encephalitis/myelitis. This complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 40 publications
(64 reference statements)
4
75
0
Order By: Relevance
“…However, this prevalence level is most likely an underestimate because some patients develop encephalitis/myelitis with positive imaging findings in the limbic area and high levels of DNA in the plasma, but are unable to undergo lumbar puncture for various clinical reasons, including severe thrombocytopenia or deteriorated general condition. 11 Ogata et al 47 reported that, in cases where lumbar puncture is not possible, CNS dysfunction concomitant with high-level HHV-6 DNA detected in plasma via real-time PCR may be used to diagnose HHV-6 encephalitis in the absence of CSF testing. This group also found that encephalitis was only associated with plasma DNA loads of 410 4 , although CNS dysfunction was associated with low levels of plasma HHV-6 DNA.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, this prevalence level is most likely an underestimate because some patients develop encephalitis/myelitis with positive imaging findings in the limbic area and high levels of DNA in the plasma, but are unable to undergo lumbar puncture for various clinical reasons, including severe thrombocytopenia or deteriorated general condition. 11 Ogata et al 47 reported that, in cases where lumbar puncture is not possible, CNS dysfunction concomitant with high-level HHV-6 DNA detected in plasma via real-time PCR may be used to diagnose HHV-6 encephalitis in the absence of CSF testing. This group also found that encephalitis was only associated with plasma DNA loads of 410 4 , although CNS dysfunction was associated with low levels of plasma HHV-6 DNA.…”
Section: Discussionmentioning
confidence: 99%
“…This group also found that encephalitis was only associated with plasma DNA loads of 410 4 , although CNS dysfunction was associated with low levels of plasma HHV-6 DNA. Mori et al 11 have diagnosed HHV-6 encephalitis when such patients meet two of the following three criteria: (1) typical clinical manifestations, (2) detection of HHV-6 DNA in the peripheral blood or (3) limbic encephalopathy based on the selective involvement of the temporal lobe on magnetic resonance imaging. It must also be recognized that high levels of HHV-6 DNA can be due to ciHHV-6, and we therefore chose not to include patients without detection of HHV-6 in the CSF in our estimation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations